The Epidemiological and Financial Effects of Pneumococcal Vaccination on Otitis Media Related Admissions in the United States. (July 2021) - Grobman, Ariel; Reddy, Priyanka; Wolfovitz, Amit; Sylvester, Michael; Angeli, Simon I.
Objective: To quantify the prevalence of hospital admissions, the financial impact, and the trends in surgical procedure rates for AOM and CAOM for all ages before and after 13-valent pneumococcal conjugate vaccine (PCV13) introduction. Methods: Retrospective analysis of the National Inpatient Sample (NIS) from 1998 to 2013 to determine the prevalence of AOM/CAOM related admissions and weighted frequencies of AOM/CAOM related International Classification of Diseases, ninth revision (ICD-9) hospital diagnoses. Prevalence of surgical procedures to treat CAOM, cost of admission, length of stay, and cost per day of admission were tabulated. Trend analysis of this data was performed. Results: A total of 46 580 patients were hospitalized with AOM in the designated time period, of which 37 366 had CAOM. The prevalence of hospital admission due to AOM had the most pronounced decrease from pre-vaccine era (1998) to post-PCV13 implementation (2013) in age group 0 to 4 (32%) followed by age group 5 to 19 (7%). Age groups 20-64 and 65+ showed slight increases in prevalence. The trend in prevalence of admissions due to CAOM mirrors that of overall admissions with an 18% and 5.8% decrease in age groups 0-4 and 5-19, respectively, and a 1% increase in ages 20+. The inflation adjusted mean cost of admission did not significantly increase between 2001 and 2013. The total cost per admission was 4428 and 7546 for those with AOM and CAOM, respectively. Mastoidectomy rates increased by 17% in hospitalized children during the post-vaccine era but decreased in the elderly population. Conclusion: The prevalence of AOM/CAOM hospital admissions decreased from the pre-vaccine era (1998) to post-PCV13 implementation (2013) in pediatric patients. Surgical procedure utilization and cost of hospital admission for AOM/CAOM did not increase throughout the study period.